In vitro Prebiotic Effect of Bread-Making Process in Inflammatory Bowel Disease Microbiome - Lluansí, Aleix; Llirós, Marc; Oliver, Lia; Bahí, Anna; Elias-Masiques, Núria; Gonzalez, Marina; Benejam, Patrícia; Cueva, Emilio; Termes, Miquel; Ramió-Pujol, Sara; Malagón, Marta; Amoedo, Joan; et al. (Frontiers in Microbiology, 2021)
Inflammatory bowel disease, including its two main categories (Crohn's disease and ulcerative colitis), has been linked either to gut microbiota or to diet. Bread is a daily food that has a potential capacity as a prebiotic. Our aim was to evaluate different breadmaking processes and their effect on fecal colonic microbiota. The microbial composition of several sourdoughs and dough samples was analyzed by high-throughput sequencing of 16S and 18S rRNAs genes. Three types of bread, which followed different breadmaking processes, were in vitro digested and incubated with feces from IBD patients. Changes in gut microbiota were assessed using a quantitative polymerase chain reaction using specific bacterial sequence targets. Short-chain fatty acids production was also analyzed by gas chromatography. Lactobacillus sanfranciscenis was the dominant lactic acid bacteria species found in sourdough and bread doughs prepared using sourdough, whereas Saccharomyces cerevisiae was the most dominant yeast in all groups, especially in bread doughs before baking. Differences in microbial composition in raw bread doughs were more related to the type of dough and elaboration than to fermentation time lengths. The analysis of in vitro fecal incubations with bread conditions revealed an increase in most biomarkers abundances and short-chain fatty acids production, both in Crohn’s disease and ulcerative colitis samples. Most remarkable increases in short-chain fatty acids production matched with higher abundances of Roseburia spp. Both best results were mainly obtained when using a high quantity of bread, regardless of bread type. Overall, this study highlights the bacterial dynamics within the breadmaking process and the effect on fecal bacteria from Inflammatory bowel disease patients.